Factors Affecting Consumption Expenditure in Ethiopia: The Case of Amhara National Regional State (ANRS) - Shimeles Mulugeta Gebreselassie; Prof. Principal Ndlovu (International Journal of Engineering and Management Research, 2020)
Background: The studies on consumption expenditure are important as it is related to poverty. Households with lowest total expenditure, a greater proportion of percentage expenditure spent on basic needs such as food and housing, then this results the household being more resources constrained (poorer) as a result. Objective: The study attempts to analyze the impact of demographic and socioeconomic characteristic of households on consumption expenditure in the Amhara National Region State (Ethiopia) using the latest Household Consumption Expenditure Survey (HCES) 2015/16. Methods: The study applied quantile regression model to identify determinants of consumption expenditure by considering per capita consumption expenditure as a dependent variable. We analyzed conditional consumption expenditure on OLS and at 7 selected quantiles: 0.05, 0.10, 0.25, 0.50, 0.75, 0.90, and 0.95 which will be denoted by , , …, and . The quantile effect of categorical variables is calculated based on Kennedy (1981) approach. Results: Households those own residential house, were headed by educated persons and whose household heads were employed (generating income) expends more. On the other hand, households headed by females expends less. Based on marital status unmarried household heads consumption expenditure is less than households who are married (or living together) at all quantiles except at the 95thquantile, while unmarried consumption expenditure is more than widowed, and divorced (or separated) at 90th& 95thquantile and 50th ,75th ,90th& 95thquantile respectively.